EXPERIMENT ON CULTURE OF MILKFISH CHANOS CHANOS (FORSKAL) IN SALT-PANS AT VEPPALODAI, TUTICORIN - Bensam, P; Marichamy, R (Indian Journal of Fisheries, 2011)
Constructing ipands in a pAmairy reservoir storing sea water in production of common salt, an experiment was carried out during 1973-74 on culture of Chanos, without undlertakifciig much management procedures or supplementary feeding, In one pond with stooktog rate of about 75,490/ha. survival wab about 44% and production was about S57 kg/ha/14 iwoirihs, while 10 another pond with stocking irate of about 7,820/ha, survival was about 85% but production was only 318 fcg/ha/11 months.